Observation of the trends of the study on the quality of water in periods of drought of the basin of the Yaracuy River and the Cumaripa reservoir (Agroindustria, Sociedad y Ambiente, 2022)
The waters of the Yaracuy River are destined for multiple uses, including irrigation, drinking water supply, agro-industrial and recreational. The main economic activities that take place in the basin are agriculture and agro-industry, identified as the main water quality problems of the Yaracuy river the dragging of sediments and organic and microbial contamination generated by the destruction of the vegetal layer and the wastewater discharges from industries and towns. In this work, the observations of the tendencies of the results of the study on the evaluation of the water quality of the Yaracuy river, mouth of the Yurubí river and the Cumaripa reservoir were made in the sampling carried out by the Ministry of the Environment in the year 2011 and compared with the water quality characteristics for each type of assigned use, established in Articles 5 and 6 of Decree 2181 "Rules for the Classification and control of the waters of the Yaracuy River basin with the interest in verifying compliance with technical, environmental and legal regulations in force in the country. The results indicate the impact of wastewater discharges from populations and companies located in the basin directly affects the quality of the waters of the Yaracuy River.
Keywords: water quality, wastewater, water quality index